Deconstructing The Stereotypes Of Women Through A Female Voice In Burial Rites (2013) By Hannah Kent - Ayuningtyas, Paramita (Lingua Cultura, 2015)
Patriarchal society regulates how women should behave and act. If a woman obeys the social rules, she will be labeled as a good woman. On the other hand, if a woman does not follow the social values, she will be immediately categorized as an evil woman and given negative stereotypes. This binary opposition between a good woman and a bad woman is often criticized by the feminists because they think this categorization burdens women. This issue is also highlighted by Hannah Kent in her novel Burial Rites (2013). This novel is set in a rural society in Iceland in the 19th century with its patriarchal values, focusing on a woman named Agnes that will soon be executed. This theme interested the researcher to study Burial Rites more deeply using feminist perspective. Characters, setting and point of view are the intrinsic elements discussed in this research. The result of the analysis shows that through these three elements, Burial Rites describes society’s stereotypes about ‘evil women’ and there is an effort from the author to deconstruct the stereotype through a female voice.